Extract of Brassica rapa suppresses ovalbumin-induced asthma by down-regulating NF-kappaB and p38 MAPK activity (Bangladesh Journal of Pharmacology, 2015)
Asthma is one of the most common chronic inflammatory diseases characterized by airway infiltration of inflammatory cells inducing hyper-responsiveness. Due to the inefficacy of currently used drugs to definitely cure asthma, there is an insistent need for identification of novel therapies. In the present research, efficiency of Brassica rapa extract in asthma-induced mouse model was investigated. Asthma was induced in mice by ovalbumin induction. The extract (125-500 mg/kg) effectively reduced ovalbumin-specific IgE in serum and levels of interleukins (IL): IL-4, IL-5 and IL-13 in bronchoalveolar lavage fluid (BALF). B. rapa extract inhibited inflammatory cell infiltration in BALF and also improved lung compliance and airway resistance. The extract caused marked reduction in the expression levels of phosphorylated ERK, p38, I?B-? and NF-?B, however dose-dependent activation of JNK was observed. The extract of B. rapa thus was effective in suppressing ovalbumin-induced asthma.